Разработка алгоритма мультиагентного управления группой мобильных "s-bot" - Ткачев, В.Н.; Токарев, В.В.; Чурюмов, Г.И. (Реєстрація, зберігання і обробка даних, 2019)
Проведено аналіз існуючих підходів до вирішення проблеми групового управління інтелектуальними мобільними об’єктами (ІМО). Дано визначення поняттям «Swarm-bot» і «s-bot». Проаналізовано основні проблеми, що виникають при управлінні групою ІМО. Показано, що при побудові «Swarm-bot»-системи найбільш важливим і складним завданням є розробка системи управління, що здатна вирішувати завдання глобального та локального планування відповідно до обраної стратегії групового управління і одержуваної «s-bot» інформацією. Наведено загальну концепцію побудови гібридної «Swarm-bot»-системи. Розроблено алгоритм мультиагентного управління групою мобільних «s-bot». Проведен анализ существующих подходов к решению проблемы группового управления интеллектуальными мобильными объектами (ИМО). Дано определение понятиям «Swarm-bot» и «s-bot». Проанализированы основные проблемы, возникающие при управлении группой ИМО. Показано, что при построении «Swarm-bot»-системы наиболее важной и сложной задачей является разработка системы управления, способной решать задачи глобального и локального планирования в соответствии с выбранной стратегией группового управления и получаемой «s-bot» информацией. Приведена об/цая концепция построения гибридной «Swarm-bot»-системы. Разработан алгоритм мультиагентного управления группой мобильных «s-bot». Currently, intelligent mobile objects (IMOs) are widely used in areas associated with risk to people, for example, in the chemical and nuclear industry in case of man-made and natural disasters, etc. The IMOs can be used in solving problems such as inspection and investigation of hard-to-reach premises, monitoring of various objects, mapping of working space pollution, security systems, etc. The advantages of using the IMO group are shown. The definition of multi-agent systems is given. The properties of the concept of «agent» are formulated. The advantages of using the IMO group are shown: longer range; extended set of functions (multi-functionality); a higher probability of accomplishing the tasks, which is achieved due to the possibility of redistributing goals between the IMO group in case of failure in some of them. The relevance of multi-agent management of the IMO group in the aftermath of the consequences of man-made accidents and disasters, where there is a destructive external influence (DEI), is formulated because DEI is one of the basic conditions for the application of a technical system in the form of an IMO in an environment that is dangerous to humans. The solution of this task is aimed at the practical implementation of multi-agent managing the IMO group, which allows to significantly reduce the degree of risk when working in adverse or dangerous conditions. The concept of «Swarm-bot» system and its separate component, a «swarm-bot», is introduced. It is shown that when building a «Swarm-bot» system, the most important and challenging task is to develop a management system capable of solving global and local planning tasks in accordance with the selected group management strategy and the received «s-bot» information. Depending on the group management strategy used, there are three types of «Swarm-bot»: centralized, decentralized, and hybrid.